2008
DOI: 10.1038/ismej.2007.106
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance in plants via habitat-adapted symbiosis

Abstract: We demonstrate that native grass species from coastal and geothermal habitats require symbiotic fungal endophytes for salt and heat tolerance, respectively. Symbiotically conferred stress tolerance is a habitat-specific phenomenon with geothermal endophytes conferring heat but not salt tolerance, and coastal endophytes conferring salt but not heat tolerance. The same fungal species isolated from plants in habitats devoid of salt or heat stress did not confer these stress tolerances. Moreover, fungal endophytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
590
2
21

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 909 publications
(626 citation statements)
references
References 36 publications
13
590
2
21
Order By: Relevance
“…In fact, in adaptive terms, a high prevalence of the fungus is not totally incompatible with a slight parasitism [54]. Alternatively, we could hypothesize that OTU01 gives, in turn, some fitness benefits to its host, as occurs in other similar cases [2,39,53]. Indeed, DSF are often related to beneficial effects on their hosts' development, including nutrient uptake, growth promotion, or tolerance to environmental stresses, although these are frequently difficult to detect [12].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in adaptive terms, a high prevalence of the fungus is not totally incompatible with a slight parasitism [54]. Alternatively, we could hypothesize that OTU01 gives, in turn, some fitness benefits to its host, as occurs in other similar cases [2,39,53]. Indeed, DSF are often related to beneficial effects on their hosts' development, including nutrient uptake, growth promotion, or tolerance to environmental stresses, although these are frequently difficult to detect [12].…”
Section: Discussionmentioning
confidence: 99%
“…As these sites were characterised by small populations (<50 individuals), a relatively open and dry environment, shallow sandy soil and a lack of vegetative competition, then the endophytes may be associated with stress tolerance in the host (Rodriguez et al 2008). Even though the measured site and plant parameters indicated that the plants were growing under at least abiotic stress, most of the plants were in reasonably good health (only three populations were classed as being in poor health, and these were not on the most saline soils) and all had flowered.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi are distributed world-wide and have been isolated from a variety of plant types including mosses, liverworts, ferns and higher plants (Higgins et al, 2007;Rosa et al, 2010;U'Ren et al, 2012). Endophytic fungi have diverse application as they may play role in plant growth (Mucciarelli et al, 2003); plant defense (Gao et al, 2010); affect plant resistance under stressful conditions (both biotic and abiotic stresses) (Marquez et al, 2007;Rodriguez et al, 2008); decompose plant litter (Sun et al, 2011). Apart from these, endophytic fungi are also known to produce many valuable bioactive metabolites including anti-microbial, anti-insect, anticancer, anti-diabetic and immunosuppressant compounds along their great potential applications in agriculture, medicine and food industry (Verma et al, 2009;Zhou et al, 2010;Zhao et al, 2011;Hema et al, 2015).…”
Section: Introductionmentioning
confidence: 99%